A process for briquette production

CN122941475APending Publication Date: 2026-10-20SHAANXI FURU ENVIRONMENTALLY FRIENDLY COAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611305500.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]针对现有技术的不足,本发明提供了一种型煤制备工艺,解决了现有型煤粘结体系中,常温流变操作窗口期与高温固化交联强度之间存在制约关系

Benefits of technology

1、本发明的制备工艺延长了混料与成型过程的操作窗口期。通过引入碳酸亚丙酯与柠檬酸螯合铝溶液作为复合固化体系,并结合20℃~30℃的湿混温度控制,使交联反应在常温混料阶段处于相对停滞状态。物料在此阶段维持了较低的粘度与适宜的流变性能,降低了因粘结剂早期固化而导致混合与压球成型设备发生粘附或堵塞的概率,有利于连续化工业生产的顺利进行。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a process for preparing briquettes. The raw materials for this process include raw coal powder, powdered alkali lignin, liquid water glass, propylene carbonate, citric acid chelated aluminum solution, and added water. During preparation, the raw coal powder and alkali lignin are dry-mixed, and the liquid components are added and wet-mixed under controlled temperature. After pressing and molding, the mixture undergoes heat treatment and air cooling to obtain the finished product. During the room-temperature mixing stage, the composite curing system does not undergo significant chemical reactions, maintaining good material flowability and thus extending the operating window. During the heat treatment stage, propylene carbonate undergoes hydrolysis upon heating, causing the system's pH value to decrease. This promotes the dehydration and condensation of water glass, and the released free aluminum ions coordinate with alkali lignin, forming an inorganic-organic composite cross-linked network between the coal powder particles. This invention reduces the risk of early curing and bonding of equipment and improves the cold compressive strength and water immersion resistance of the finished briquettes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coal deep processing and resource utilization technology, specifically a coal briquette preparation process. Background Technology

[0002] Processing industrial pulverized coal or low-rank crushed coal into briquettes is an effective way to improve coal resource utilization, combustion efficiency, and reduce dust pollution. During briquette preparation, the selection and compatibility of the binder directly determine the mechanical strength, thermal stability, and moisture and water resistance of the finished product. To comprehensively improve the various physicochemical properties of briquettes, industrial processes often employ a combination of inorganic binders (such as water glass and bentonite) and organic binders (such as lignin and starch).

[0003] When using a composite bonding system of water glass and alkali lignin, acidic substances or polyvalent metal salts are usually introduced as curing agents to ensure a stable bond between the two coal powder particles. This promotes the dehydration and condensation of water glass and guides the cross-linking of lignin molecules. However, in actual continuous preparation processes, there is an irreconcilable contradiction between the rheological operating window of this composite system and the cured strength of the finished product.

[0004] If highly reactive acids or free metal ion curing agents are added directly during the mixing stage, the pH value of the system will change rapidly, causing water glass and alkali lignin to react prematurely at room temperature. This early curing phenomenon will cause the viscosity of the wet-mixed material to rise sharply in a short period of time, resulting in the material losing the plasticity and fluidity required for pressing and molding. This not only severely shortens the process operating window, but also easily causes adhesion in the mixing equipment and blockage in the roller briquetting machine, affecting the continuity of production.

[0005] Conversely, to maintain the low viscosity of the material at room temperature and ensure smooth molding, some processes reduce the amount of crosslinking curing agent added or use low-reactivity binder formulations. However, this treatment method prevents the formed wet-based briquettes from undergoing deep chemical crosslinking reactions, and their hardening process mainly relies on the physical evaporation of moisture. The physical bonding structure formed solely by dehydration and drying is relatively loose and cannot build a dense network skeleton inside the briquettes, ultimately resulting in low cold compressive strength of the finished briquettes. Furthermore, due to the presence of numerous hydrophilic micropores, this type of briquettes is prone to water absorption, swelling, and structural collapse when exposed to rainwater during open-air storage and transportation, failing to meet the requirements of actual industrial applications for the mechanical strength and water resistance of briquettes. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a briquette preparation process that resolves the constraint between the room-temperature rheological operating window and the high-temperature curing crosslinking strength in existing briquette bonding systems. Highly reactive binder systems are prone to early curing during mixing and molding, leading to a surge in material viscosity and subsequent equipment blockage; while low-reactive binder systems require extended drying times and suffer from poor curing strength, water resistance, and thermal stability in the final briquette product.

[0007] To achieve the above objectives, the present invention provides a briquette preparation process, which employs the following technical solution: A process for preparing briquettes, using raw materials comprising the following parts by weight: Powdered coal: 100 parts; Powdered alkali lignin: 2-5 parts; Liquid water glass: 3-6 parts; Propylene carbonate: 0.3–0.8 parts; Citric acid chelated aluminum solution: 0.5–1.2 parts; And add water; The preparation process includes the following steps: S1. Dry mixing: The raw coal powder and powdered alkali lignin weighed according to the proportion are added to the mixer for dry mixing; S2. Wet mixing: Simultaneously spray the liquid water glass, propylene carbonate, aluminum chelate citrate solution and water into the dry mixture, and continuously wet mix at a controlled temperature to obtain a wet mixture. S3. Molding: The wet mixture is fed into a molding device and pressed under pressure to obtain wet-based coal briquettes; S4. Solidification: The wet coal briquettes are transported to a drying device and heat-treated at a set inlet air temperature. S5. Cooling: The heat-treated briquettes are cooled by forced air cooling and then screened to obtain the finished briquettes.

[0008] By adopting the above technical solution, the briquette preparation process of the present invention can keep the material in a relatively stable rheological state during the room temperature mixing stage, and reduce the risk of equipment adhesion caused by early cross-linking; then, in the heat curing stage, the chemical reaction is triggered by temperature change, thereby improving the mechanical properties and water resistance of the finished briquette.

[0009] The reaction mechanism of this process mainly includes the following steps: During the dry and wet mixing stages, the material system exhibits a certain alkaline environment due to the presence of water glass and alkali lignin. Under these ambient temperature conditions, the propylene carbonate and citric acid chelated aluminum solution do not undergo significant dissociation or hydrolysis reactions. At this time, citric acid molecules coordinate and mask aluminum ions, allowing the water glass system to maintain a sol state. The components are mainly physically dispersed during this stage, maintaining a relatively low viscosity and thus providing flowability support for subsequent compression molding operations.

[0010] During the curing heat treatment stage, as the internal temperature of the briquettes gradually rises, propylene carbonate absorbs heat and undergoes ring-opening hydrolysis. This hydrolysis reaction consumes some hydroxide ions in the system, generating propylene glycol and carbonate, which in turn leads to a decrease in the pH value of the microenvironment inside the briquettes. With the decrease in system pH and continuous heat input, the coordination equilibrium within the pre-set citrate-chelated aluminum system is gradually disrupted, and the citrate ligands begin to detach, releasing free aluminum ions.

[0011] Meanwhile, the decrease in pH and the evaporation of water accelerate the dehydration and condensation of metasilicate ions in water glass, thereby generating an inorganic rigid framework mainly composed of Si-O-Si bonds. During this process, the released aluminum ions can coordinate with phenolic hydroxyl and carboxyl groups in the alkali lignin molecular structure, forming corresponding aluminum-oxygen-carbon crosslinking nodes, which in turn crosslink to form a flexible organic polymer network.

[0012] The aforementioned inorganic silicate framework and organic lignin network develop synchronously within the micropores of the briquettes, exhibiting a degree of interpenetration and entanglement. Furthermore, the hydrolysis byproduct propylene glycol remains in the network interstices, providing moderate lubrication and plasticizing effects. This composite network structure helps to fix the raw coal powder particles, reduces the channels for moisture infiltration, and thus improves the cold compressive strength of the briquettes and the strength retention rate after water immersion.

[0013] Preferably, the raw coal powder has a particle size ≤3.0mm, wherein the mass fraction of particles with a particle size ≤1.0mm is ≥70wt%; the liquid water glass has a modulus of 2.4 to 3.2 and a Baume degree of 40Bé to 45Bé; the powdered alkali lignin has a number average molecular weight of 3000g / mol to 5000g / mol, and the pH value of a 1wt% aqueous solution of the powdered alkali lignin is 9.5 to 11.0.

[0014] By employing the above technical solutions, controlling the proportion of fine particles in the raw coal powder helps it form a relatively compact packing state during the pressing process, reducing internal voids. Using water glass with a specific modulus and Baumé degree provides the basic silicate oligomers for the system. Limiting the molecular weight parameters of lignin is primarily to obtain suitable segment lengths and active functional group distributions, making it easier for it to unfold in the aqueous system and mix with inorganic components.

[0015] Preferably, the citrate-chelated aluminum solution is prepared by the following steps: A1. Prepare a citric acid aqueous solution with a mass concentration of 30 wt%; A2. Under mechanical stirring at room temperature, add aluminum sulfate crystals octadechydrate until completely dissolved to form an acidic complex solution with a molar ratio of aluminum ions to citric acid molecules of 1:(1.5~2.0); A3. Under the condition of maintaining the system temperature not exceeding 30°C, slowly add a 20wt% sodium hydroxide aqueous solution to the acidic complex solution. Stop adding the solution when the pH value of the system rises to 10.5-11.0, and continue stirring at 30°C for 60 minutes to obtain a citrate chelated aluminum solution.

[0016] By employing the above technical solution, a specific ratio of citric acid is used to promote the coordination and masking effect of aluminum ions. Adding alkaline solution dropwise at a lower temperature and then aging the mixture aims to adjust the initial pH of the complexing solution to be close to that of the wet mixture, thereby reducing localized acid-base neutralization caused by the addition of the aluminum-containing solution and thus lowering the possibility of premature silica gel precipitation from water glass.

[0017] Preferably, the raw coal powder is dried and homogenized before being weighed, so that the initial moisture content of the raw coal powder when it is actually fed is controlled to be 3.0wt% to 5.0wt%.

[0018] By adopting the above technical solution, the impact of moisture fluctuations in raw coal between different batches can be mitigated. Maintaining a relatively stable initial moisture content can promote the initial adhesion of powdered alkali lignin to the coal powder surface, providing better spreading conditions for the subsequently added liquid phase components.

[0019] Preferably, in step S1, the mixer is a twin-shaft paddle mixer with a rotation speed of 40 r / min to 60 r / min and a dry mixing time of 3 min to 5 min. By adopting the above technical solution, the shearing action of the mixing equipment helps to disperse the soft agglomeration phenomenon in the raw coal powder and alkali lignin, and promotes the initial uniformity of the solid powder materials.

[0020] Preferably, in step S2, the water cooling system is turned on to control the material mixing temperature to 20℃~30℃; the amount of water to be added is calculated based on the measured initial moisture content of the raw coal powder and the moisture content of the liquid components, so that the moisture content of the wet mixture is 8.0wt%~12.0wt%, and the wet mixing time is 10 minutes~15 minutes.

[0021] By adopting the above technical solutions, controlling the mixing temperature helps to remove the heat generated during the stirring process, reducing the probability of premature hydrolysis of propylene carbonate due to temperature rise. By calculating and adjusting the moisture content of the wet mixture, a certain solvent medium is provided for the mass transfer and diffusion of the liquid phase components, while avoiding the problems of excessive material plasticity and difficulty in demolding caused by high water content.

[0022] Preferably, in step S3, a double-roller briquetting machine is used as the forming equipment, and the pressing linear pressure is set to 20MPa~30MPa, and the roller speed is 10r / min~15r / min.

[0023] By employing the above technical solution, mechanical compression causes a certain degree of displacement and rearrangement of the raw coal powder particles, helping to expel some of the air trapped inside the material. This linear pressure parameter is adapted to the state of the wet mixture, enabling the wet-based briquettes to obtain basic mechanical strength that facilitates subsequent handling and transmission.

[0024] Preferably, in step S4, a mesh belt through-flow dryer is used as the drying equipment, the inlet air temperature is set to 110℃~130℃, and the heat treatment time is 25 minutes~45 minutes; at the end of the heat treatment, the center temperature of the briquettes is controlled to reach above 95℃.

[0025] By adopting the above technical solution, the selected hot air temperature range can form a temperature gradient during the heat transfer process from the surface to the interior of the briquettes, providing the necessary thermal energy for the hydrolysis of propylene carbonate. Setting the heat treatment duration and target center temperature aims to increase the extent of the internal cross-linking reaction and accelerate the construction of the network framework.

[0026] Preferably, in step S5, the solidified briquettes enter the counter-current cooling section, where the center temperature of the briquettes is reduced to below 40°C under forced air cooling, and the moisture content of the finished briquettes is ≤3.0wt%.

[0027] By adopting the above technical solution, forced air cooling can rapidly cool the briquettes, thereby delaying and essentially stopping subsequent internal reactions. During the cooling process, as the temperature drops below the glass transition temperature of the lignin segments, their state changes and a certain hardening effect occurs. Combined with the inorganic skeleton structure and by controlling the moisture content of the final product at a low level, this helps the cross-linked network to dehydrate, shrink, and close, achieving the final strength shaping of the briquettes.

[0028] This invention provides a process for preparing coal briquettes. It has the following beneficial effects: 1. The preparation process of this invention extends the operating window period of the mixing and molding processes. By introducing propylene carbonate and citric acid chelated aluminum solution as a composite curing system, and combining it with wet mixing temperature control of 20℃~30℃, the crosslinking reaction is kept relatively stagnant during the room temperature mixing stage. The material maintains low viscosity and suitable rheological properties during this stage, reducing the probability of adhesion or blockage in the mixing and briquetting equipment due to early curing of the binder, which is beneficial for the smooth operation of continuous industrial production.

[0029] 2. The technical solution of this invention can improve the cold compressive strength of the final briquettes. During the curing heat treatment stage, as the inlet air temperature increases, propylene carbonate undergoes hydrolysis upon heating, lowering the pH value of the material system. This, in turn, promotes the dehydration and condensation of water glass to form an inorganic silicate framework. Simultaneously, the free aluminum ions released from the decomplexing react with alkali lignin to form an organic network. This composite cross-linked structure formed between the inorganic and organic components and the raw coal powder particles increases the bonding force between the coal powder particles, resulting in better macroscopic mechanical strength in the finished briquettes.

[0030] 3. This invention improves the water resistance of finished briquettes. During the heat treatment and curing process, the inorganic silicate skeleton formed by the dehydration and condensation of water glass and the organic flexible segments formed by the coordination crosslinking of aluminum ions and lignin are simultaneously generated and intertwined within the micropores of the briquettes. This composite network structure fills and seals the internal voids of the briquettes to a certain extent, cutting off the capillary channels through which external moisture permeates into the interior. Combined with the network dehydration shrinkage effect resulting from controlling the residual moisture content to below 3.0 wt% in the process, the water absorption and swelling phenomenon of the briquettes in a water-contaminated environment is reduced, thereby improving their strength retention rate after immersion in water and reducing the likelihood of them collapsing when exposed to water. Attached Figure Description

[0031] Figure 1 Fourier transform infrared spectra of the samples prepared in Example 1 and Comparative Example 3 of the present invention; Figure 2 The following are thermal stability test diagrams of the samples of Example 1 and Comparative Example 1 of the present invention, wherein (a) is a thermogravimetric curve and (b) is a differential scanning calorimetry curve. Figure 3 The rheological test diagrams of the mixed slurry in Example 1 and Comparative Example 2 of the present invention are shown, where (a) is a curve of the apparent viscosity of the slurry changing with time, and (b) is a curve of the control program of the rheometer system temperature changing with time. Figure 4The following are test graphs of the flowability and operating window period of the mixtures in the embodiments and comparative examples of the present invention, wherein (a) is a bar chart comparing the rheological operating window period, and (b) is a line graph showing the change of the slump expansion of the mixture with the test time. Figure 5 The figures show a comparison of the cold physical strength tests of the briquettes in the embodiments and comparative examples of the present invention. (a) shows the drop strength test results of each group of briquettes, and (b) shows the cold compressive strength test results of each group of briquettes. Figure 6 The following are water resistance test results of the briquette products in the embodiments and comparative examples of the present invention. (a) is a test result of the cold compressive strength of the briquette sample after immersion for 24 hours, and (b) is a test result of the water strength retention rate of each group of briquette samples. Figure 7 This is a comparison diagram of the compressive strength of coal samples before and after high-temperature roasting in the embodiments and comparative examples of the present invention. Detailed Implementation

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] This invention provides a coal briquette preparation process. The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products: The raw coal powder used in the experiment was obtained by crushing and screening commercially available anthracite. Its particle size distribution was controlled to be ≤3.0mm, of which the mass fraction of particles ≤1.0mm was ≥70wt%. Before use, it was pre-dried and homogenized to control the initial moisture content of the material to be 3.0wt% to 5.0wt% when it was actually fed into the material. In each example and comparative example, the amount of water to be added was calculated based on the measured initial moisture content of the raw coal powder and the moisture content of the liquid components to ensure that the total moisture content of the material after wet mixing reached the corresponding set value.

[0034] The chemical name of liquid water glass is sodium silicate aqueous solution, CAS number 1344-09-8, molecular formula Na2O·nSiO2, commercially available industrial grade product is selected, its modulus (molar ratio of SiO2 to Na2O) ranges from 2.4 to 3.2, and its Baume degree is between 40 Bé and 45 Bé.

[0035] The organic binder uses powdered alkali lignin, CAS number 8068-05-1, which is a three-dimensional network amorphous natural polystyrene derivative whose main chain is linked by carbon-carbon bonds and ether bonds. The selected product has a number average molecular weight Mn of 3000 g / mol to 5000 g / mol, and its 1 wt% aqueous solution has a pH value between 9.5 and 11.0, with a purity of ≥95.0 wt% on a dry basis.

[0036] The latent curing agent propylene carbonate (CAS No. 108-32-7, purity ≥99.0wt%), aluminum sulfate octahydrate (CAS No. 7784-31-8, purity ≥99.0wt%) and citric acid monohydrate (CAS No. 5949-29-1, purity ≥99.5wt%) used to synthesize latent metal crosslinking precursors, and sodium hydroxide (CAS No. 1310-73-2, purity ≥99.0wt%), a pH adjuster, are all commercially available conventional chemical reagents. Their chemical structural characteristics are unique and well-known in the field, and they can be purchased and used directly.

[0037] Preparation Example 1: This preparation example provides a method for preparing a citric acid chelated aluminum solution used in a briquette preparation process, comprising the following steps: Weigh 36.77g of citric acid monohydrate and dissolve it in 85.80g of deionized water to prepare a citric acid aqueous solution with a mass concentration of 30wt%. At room temperature (25℃) and mechanical stirring at 200 r / min, 33.32 g of aluminum sulfate octahydrate crystals were slowly added in batches to the above citric acid aqueous solution. The mixture was stirred for 30 minutes until the crystals were completely dissolved, forming a transparent acidic complex solution. At this time, the molar ratio of aluminum ions to citric acid molecules in the system was 1:1.75. Turn on the water cooling jacket of the reactor to maintain the system temperature not exceeding 30°C. Slowly add a 20wt% sodium hydroxide aqueous solution to the above acidic complex solution while continuously stirring. At the same time, dynamically monitor the pH value of the system. Stop adding the solution when the pH value rises to 10.8. Continue to maintain the temperature at 30℃ and stir for 60 minutes to age the product, obtaining a uniform, transparent, light yellow liquid, which is the desired citrate chelated aluminum solution.

[0038] Preparation Example 2: This preparation example provides a method for preparing a citric acid chelated aluminum solution used in a briquette preparation process, comprising the following steps: Weigh 31.52g of citric acid monohydrate and dissolve it in 73.55g of deionized water to prepare a citric acid aqueous solution with a mass concentration of 30wt%. At room temperature (25℃) and mechanical stirring at 200 r / min, 33.32 g of aluminum sulfate octahydrate crystals were slowly added in batches to the above citric acid aqueous solution. The mixture was stirred for 30 minutes until the crystals were completely dissolved, forming a transparent acidic complex solution. At this time, the molar ratio of aluminum ions to citric acid molecules in the system was 1:1.5. Turn on the water cooling jacket of the reactor to maintain the system temperature not exceeding 30°C. Slowly add a 20wt% sodium hydroxide aqueous solution to the above acidic complex solution while continuously stirring. At the same time, dynamically monitor the pH value of the system. Stop adding the solution when the pH value rises to 10.5. The mixture was kept at 30℃ and stirred for 60 minutes for aging, resulting in a homogeneous, transparent, pale yellow liquid, which is the desired aluminum citrate chelate solution. After weighing and calculation, the total mass of the obtained aluminum citrate chelate solution was 288.39 g, of which Al was the dominant component. 3+ The concentration was calculated to be 0.35 mol / kg.

[0039] Preparation Example 3: This preparation example provides a method for preparing a citric acid chelated aluminum solution used in a briquette preparation process, comprising the following steps: Weigh 42.03g of citric acid monohydrate and dissolve it in 98.07g of deionized water to prepare a citric acid aqueous solution with a mass concentration of 30wt%. At room temperature (25℃) and mechanical stirring at 200 r / min, 33.32 g of aluminum sulfate octahydrate crystals were slowly added in batches to the above citric acid aqueous solution. The mixture was stirred for 30 minutes until the crystals were completely dissolved, forming a transparent acidic complex solution. At this time, the molar ratio of aluminum ions to citric acid molecules in the system was 1:2.0. Turn on the water cooling jacket of the reactor to maintain the system temperature not exceeding 30°C. Slowly add a 20wt% sodium hydroxide aqueous solution to the above acidic complex solution while continuously stirring. At the same time, dynamically monitor the pH value of the system. Stop adding the solution when the pH value rises to 11.0. The mixture was kept at 30℃ and stirred for 60 minutes for aging, resulting in a homogeneous, transparent, pale yellow liquid, which is the desired aluminum citrate chelate solution. After weighing and calculation, the total mass of the obtained aluminum citrate chelate solution was 353.42 g, of which Al... 3+ The concentration was calculated to be 0.28 mol / kg.

[0040] Example 1: This embodiment provides a coal briquette preparation process, including the following steps: Add 100 kg of raw coal powder and 3.5 kg of powdered alkali lignin to a twin-shaft paddle mixer and dry mix for 4 minutes at a speed of 50 r / min at room temperature. The water cooling system of the mixing equipment was turned on to control the material mixing temperature at 25°C. 4.5 kg of liquid water glass, 0.5 kg of propylene carbonate, and 0.8 kg of the citric acid chelated aluminum solution prepared in Example 1 were simultaneously sprayed into the dry mixed material through an atomizing nozzle. Deionized water was added according to the measured initial moisture content of the raw coal powder, the moisture content of the liquid water glass, and the moisture content of the citric acid chelated aluminum solution to adjust the final total moisture content of the material to 10.0 wt%. Wet mixing was continued for 12 minutes. The wet mixture is fed into a double-roller briquetting machine via a feeder, and pressed under a linear pressure of 25MPa and a roller speed of 12r / min to obtain wet-based briquettes. The wet-based coal briquettes are transported to a mesh belt through-flow dryer and heat-treated for 35 minutes at an inlet air temperature of 120℃ for in-situ cross-linking and solidification. At the end of the heat treatment, the center temperature of the coal briquettes reaches above 95℃, and the residual moisture content of the finished product is controlled below 3.0wt%. After solidification, the briquettes enter the counter-current cooling section, where the temperature at the center of the briquettes is reduced to below 40°C under forced air cooling. After screening, the finished briquettes are obtained.

[0041] Example 2: This embodiment provides a coal briquette preparation process, including the following steps: 100 kg of raw coal powder and 2.0 kg of powdered alkali lignin were added to a twin-shaft paddle mixer and dry-mixed at 40 r / min for 5 minutes at room temperature. The water cooling system of the mixing equipment was turned on to control the material mixing temperature at 20°C. 3.0 kg of liquid water glass, 0.3 kg of propylene carbonate, 0.5 kg of the citric acid chelated aluminum solution prepared in Example 2, and water were simultaneously sprayed into the dry-mixed material through atomizing nozzles to adjust the final total moisture content of the material to 8.0 wt%. Wet mixing was continued for 15 minutes. The wet-mixed material was fed into a double-roller briquetting machine through a feeder and pressed under a linear pressure of 20 MPa and a roller speed of 10 r / min to obtain wet-based briquettes. The wet-based coal briquettes are transported to a mesh belt through-flow dryer and heat-treated at an inlet air temperature of 110℃ for 45 minutes to achieve in-situ cross-linking and curing. After solidification, the briquettes enter the counter-current cooling section, where the temperature at the center of the briquettes is reduced to below 40°C under forced air cooling. After screening, the finished briquettes are obtained.

[0042] Example 3: This embodiment provides a coal briquette preparation process, including the following steps: Add 100 kg of raw coal powder and 5.0 kg of powdered alkali lignin to a twin-shaft paddle mixer and dry mix for 3 minutes at a speed of 60 r / min at room temperature. Turn on the water cooling system of the mixing equipment to control the material mixing temperature at 30°C. Simultaneously spray 6.0 kg of liquid water glass, 0.8 kg of propylene carbonate, 1.2 kg of the citric acid chelated aluminum solution prepared in Example 3, and add water to the dry mixed material through an atomizing nozzle to adjust the total water content of the final material to 12.0 wt%. Continue wet mixing for 10 minutes. The wet mixture is fed into a double-roller briquetting machine via a feeder and pressed under a linear pressure of 30MPa and a roller speed of 15r / min to obtain wet-based briquettes; the wet-based briquettes are then conveyed to a mesh belt through-flow dryer and heat-treated at an inlet air temperature of 130℃ for 25 minutes to achieve in-situ cross-linking and curing. After solidification, the briquettes enter the counter-current cooling section, where the temperature at the center of the briquettes is reduced to below 40°C under forced air cooling. After screening, the finished briquettes are obtained.

[0043] Example 4: This embodiment provides a coal briquette preparation process, including the following steps: Add 100 kg of raw coal powder and 2.5 kg of powdered alkali lignin to a twin-shaft paddle mixer and dry mix at 50 r / min for 4 minutes at room temperature. Turn on the water cooling system of the mixing equipment to control the material mixing temperature at 25°C. Simultaneously spray 5.5 kg of liquid water glass, 0.7 kg of propylene carbonate, 0.6 kg of the citric acid chelated aluminum solution prepared in Example 1, and add water to the dry mixed material through an atomizing nozzle to adjust the total water content of the final material to 10.0 wt%. Continue wet mixing for 12 minutes. The wet mixture is fed into a double-roller briquetting machine via a feeder, and pressed under a linear pressure of 25MPa and a roller speed of 12r / min to obtain wet-based briquettes. The wet-based briquettes are then transported to a mesh belt through-flow dryer and heat-treated for 35 minutes at an inlet air temperature of 120℃ for in-situ cross-linking and solidification. At the end of the heat treatment, the center temperature of the briquettes reaches above 95℃, and the residual moisture content of the finished product is controlled below 3.0wt%. After solidification, the briquettes enter the counter-current cooling section, where the temperature at the center of the briquettes is reduced to below 40°C under forced air cooling. After screening, the finished briquettes are obtained.

[0044] Example 5: This embodiment provides a coal briquette preparation process, including the following steps: 100 kg of raw coal powder and 4.5 kg of powdered alkali lignin were added to a twin-shaft paddle mixer and dry-mixed at 50 r / min for 4 minutes at room temperature. The water cooling system of the mixing equipment was turned on to control the material mixing temperature at 25°C. 3.5 kg of liquid water glass, 0.4 kg of propylene carbonate, 1.0 kg of the citric acid chelated aluminum solution prepared in Example 1, and water were simultaneously sprayed into the dry-mixed material through atomizing nozzles to adjust the final total moisture content of the material to 10.0 wt%. Wet mixing was continued for 12 minutes. The wet-mixed material was fed into a double-roller briquetting machine through a feeder and pressed under a linear pressure of 25 MPa and a roller speed of 12 r / min to obtain wet-based briquettes. The wet-based coal briquettes are transported to a mesh belt through-flow dryer and heat-treated for 35 minutes at an inlet air temperature of 120℃ for in-situ cross-linking and solidification. At the end of the heat treatment, the center temperature of the coal briquettes reaches above 95℃, and the residual moisture content of the finished product is controlled below 3.0wt%. After solidification, the briquettes enter the counter-current cooling section, where the temperature at the center of the briquettes is reduced to below 40°C under forced air cooling. After screening, the finished briquettes are obtained.

[0045] Comparative Example 1: Compared with Example 1, the difference is that propylene carbonate and aluminum chelate solution were not added, and the total moisture content of the material after wet mixing was controlled at 10.0 wt% by adjusting the amount of water added; all other aspects are the same.

[0046] Comparative Example 2: Compared with Example 1, the difference is that 0.5 kg of propylene carbonate is replaced with a conventional free acid aqueous solution (acetic acid aqueous solution with a mass concentration of 10 wt%) with an equimolar acid production, and the amount of water added is reduced accordingly so that the total moisture content of the material after wet mixing is still controlled at 10.0 wt%; all other aspects are the same.

[0047] Comparative Example 3: Compared with Example 1, the difference is that no citric acid chelated aluminum solution was added, and the total moisture content of the material after wet mixing was controlled at 10.0 wt% by adjusting the amount of water added; all other aspects are the same.

[0048] Comparative Example 4: Compared to Example 1, the difference lies in replacing the 0.8 kg citrate-chelated aluminum solution with an aqueous solution of aluminum sulfate octahydrate containing equimolar amounts of aluminum ions. 3+ The molar amount of Al in the citrate chelated aluminum solution obtained in Example 1 was compared with that in 0.8 kg of the solution. 3+ The molar amounts were the same, and the total moisture content of the material was controlled at 10.0 wt% after wet mixing by adjusting the amount of water added; all other aspects were the same.

[0049] Comparative Example 5: Compared with Example 1, the difference is that the heat treatment inlet air temperature in the mesh belt through-flow dryer is set to 80°C, and the total moisture content of the material after wet mixing is still controlled at 10.0 wt%, while the rest are the same.

[0050] Test Example 1: Take the briquettes prepared in Example 1 and Comparative Example 3 respectively, select the central part of the briquettes and grind them into powder using an agate mortar and pestle, and pass them through a 200-mesh standard sieve.

[0051] The sieved powder sample was placed in a vacuum drying oven and dried at 60°C for 24 hours to remove the physically adsorbed moisture on the surface.

[0052] Weigh approximately 2.1 mg of the dried sample powder and add it to 197.5 mg of spectroscopically pure potassium bromide powder. Place the powder in an agate mortar and grind it continuously in one direction for 3 to 5 minutes until it is evenly mixed.

[0053] The mixture is transferred into an infrared tableting mold and pressed into a uniformly thick, semi-transparent sheet by using a hydraulic press at a pressure of 15 MPa for 2 minutes.

[0054] The thin slice was placed in the sample cell of the Fourier transform infrared spectrometer, and the test wavenumber range was set to 4000 cm⁻¹. -1 Up to 400cm -1 The resolution is 4cm. -1 The scan was performed 32 times, and background subtraction was performed using blank potassium bromide pellets as the background to collect absorption spectral data.

[0055] Table 1. Statistical table of wavenumbers of main characteristic peaks in infrared spectra of samples from Example 1 and Comparative Example 3 According to Table 1 and Figure 1 The difference between Example 1 and Comparative Example 3 in the characteristic absorption band can be observed. At 1080cm... -1 Nearby, both samples showed Si-O-Si asymmetric stretching vibration peaks, indicating that the water glass underwent dehydration and condensation under this heat treatment process, forming an inorganic silica gel network in both samples.

[0056] At 3400cm -1 Nearby, the OH stretching vibration peak of the phenolic hydroxyl group in lignin in Comparative Example 3 is broader and has a higher wavenumber, while the corresponding peak in Example 1 shifts to 3387.6 cm⁻¹. -1 The peak shape narrows. Meanwhile, in the spectrum of Example 1, the peak at 542.7 cm⁻¹... -1 An Al-O coordination bond vibration peak was detected at the peak, but this absorption band was not seen in the spectrum of Comparative Example 3.

[0057] This indicates that in the heated and pH-decreasing environment of the system in Example 1, the latent crosslinking precursor undergoes decomplexation and releases coordination-active aluminum species, which can form Al-O coordination structures with the hydroxyl functional groups on the organic lignin molecular chain. This demonstrates the simultaneous occurrence of inorganic polycondensation and organic coordination crosslinking processes under thermally triggered curing conditions.

[0058] Test Example 2: Take the fully cured coal briquette samples prepared in Example 1 and Comparative Example 1, take the core material without the surface hardening layer, crush it with a pulverizer, grind it in an agate mortar, and pass it through a 200-mesh standard sieve to obtain test powder.

[0059] The sieved powder sample was spread evenly in a glass petri dish and placed in a vacuum drying oven, where it was dried at 80℃ and -0.09MPa for 12 hours.

[0060] In a constant temperature and humidity environment, 8.26 mg of Example 1 sample and 8.14 mg of Comparative Example 1 sample were weighed using a microbalance, spread evenly on the bottom of a dry alumina crucible, and then covered and pressed into tablets.

[0061] The alumina crucible was placed in the heating furnace of the thermogravimetric-differential scanning calorimetry (TGC) instrument, with an empty alumina crucible of the same specifications used as a reference.

[0062] The test system was set up with high-purity nitrogen as both protective and purging gas, with a flow rate controlled at 50 mL / min. The programmed temperature rise parameters were set to an initial temperature of 30℃, linearly heating to 800℃ at a rate of 10℃ / min. Sample mass changes and heat flux data were recorded simultaneously during the test. The initial thermal decomposition temperature was determined using the tangent extrapolation method from the TG curve, the temperature corresponding to the maximum weight loss rate was determined by the peak temperature of the DTG curve, and the peak temperature of the main endothermic peak in the DSC curve was determined by the peak position of the main endothermic peak in the heat flux curve.

[0063] Table 2. Thermogravimetric-Differential Scanning Calorimetry Data of Samples from Example 1 and Comparative Example 1 According to Table 2 and Figure 2 Differences in the pyrolysis process and thermodynamic parameters between Example 1 and Comparative Example 1 can be observed.

[0064] In Figure (a), the weight loss of the Comparative Example 1 sample started earlier, with obvious thermal degradation occurring at 245.8 °C; the initial thermal decomposition temperature of Example 1 was delayed to 287.4 °C, and the mass retention rate was consistently higher than that of Comparative Example 1 throughout the entire heating range. By the end of the heating range at 800 °C, the residual mass fraction of Example 1 was 12.17 percentage points higher than that of Comparative Example 1.

[0065] In Figure (b), the main endothermic peak reflecting polymer backbone breakage and volatile matter analysis shifted by 57.6°C to the high-temperature region in Example 1. The aforementioned data indicate that the interpenetrating cross-linked structure of the inorganic silica gel network and the organic lignin coordination network in the briquette system restricts the free movement of polymer chain segments under heating conditions, slows down the decomposition and escape of the organic phase, alters the physical property of the free binder matrix being easily pyrolyzed at low temperatures, and maintains the structural integrity of the system under high-temperature conditions.

[0066] Test Example 3: In the wet mixing steps of Example 1 and Comparative Example 2, after the liquid component was sprayed in and mixed for 1 minute, 150g of the wet mixed slurry was taken as a rheological test sample.

[0067] The extracted slurry sample was placed in the parallel plate testing system of the rotational rheometer, with the parallel plate spacing set to 1.5 mm. Excess sample at the edges was scraped off, and a light silicone oil was applied to the outer edge of the sample to prevent premature evaporation of moisture during the test.

[0068] The rheometer is set to steady-state shear mode with a constant shear rate of 5 s. -1 Record the apparent viscosity data of the system.

[0069] The instrument's temperature control program is set as follows: The first stage is the isothermal holding stage, where the temperature is controlled at 25℃ and kept constant for 15 minutes to simulate the normal temperature operation window of industrial biaxial mixing and feeding; the second stage is the programmed temperature rise stage, where the temperature is linearly heated from 25℃ to 120℃ at a rate of 5℃ / min and held at this temperature for 5 minutes to simulate the heat curing process in a mesh belt dryer.

[0070] Table 3. Apparent viscosity data of the mixed slurry of Example 1 and Comparative Example 2 under programmed temperature variation conditions. According to Table 3 and Figure 3 The rheological testing process revealed stage-wise changes. In Comparative Example 2, after the addition of conventional free acid (acetic acid), the apparent viscosity of the slurry jumped from 68.7 Pa·s to 352.4 Pa·s in the initial stage of the isothermal mixing phase at 25°C (after 3.5 min), indicating unplanned premature gelation. This corresponds to the problems of equipment sticking and loss of material flowability encountered in actual industrial production. In Example 1, the viscosity remained at a low level of around 45 Pa·s within the room temperature range of 0 to 15 minutes, and then showed a slight softening and viscosity reduction with physical heating in the subsequent medium temperature range (up to 65.2°C). Only after the system temperature exceeded the high-temperature threshold of 100°C did the apparent viscosity of Example 1 increase sharply, rapidly climbing to 565.2 Pa·s at 120°C.

[0071] The test data above verified that the composite crosslinking system composed of propylene carbonate and latent aluminum chelate is chemically inert at room temperature and medium temperature, and the hydrolysis release behavior is suppressed by the steric hindrance effect, ensuring the flow operation window during the mixing stage. At the set heat treatment temperature, propylene carbonate undergoes thermally triggered ring-opening hydrolysis and gradually reduces the alkalinity of the system. The citric acid chelate aluminum system simultaneously releases aluminum species with crosslinking activity, completing the transformation of the material from liquid to solid crosslinking network.

[0072] Test Example 4: According to the solid components and dry mixing parameters described in Examples 1 to 5 and Comparative Examples 2 and 4, the corresponding dry mixed materials were prepared at room temperature.

[0073] Each group of dry-mixed materials was transferred into a laboratory-grade biaxial kneader equipped with a torque measurement module, and the circulating water cooling system was turned on to control the material temperature to the corresponding parameters set for each case.

[0074] Start the kneader and spray the liquid components as set in each example. Record the moment the liquid components are completely added as the starting point for timing, and monitor and record the running torque of the kneader's main shaft in real time. When the monitored torque value reaches three times the initial stable torque, it is determined that the slurry has entered a stage of rapid thickening and significant loss of stable fluidity. Record the time elapsed during this process as the rheological operation window of the material.

[0075] At the 5th, 15th, and 30th minute after the start of the timing, the machine was stopped and 250g of mixed slurry was taken out and filled into a standard micro slump cone. After compaction, the slump cone was lifted vertically at a uniform speed, and the maximum and minimum diameters of the slurry after it naturally spread and came to rest were measured. The average value was calculated as the slump expansion at that time point.

[0076] Table 4. Operating window and slump expansion test data of mixtures from the examples and comparative examples According to Table 4 and Figure 4 The test results showed significant differences in the engineering mixing and molding operation time among the groups. The operating window periods of Examples 1 to 5 ranged from 36.5 to 48.3 minutes, and the slump expansion of the material maintained a gradual decline trend over the 30-minute test period, remaining above 86.1 mm, indicating that the slurry was in a good plastic state.

[0077] Conversely, Comparative Example 2, which added conventional aqueous free acid, and Comparative Example 4, which added conventional aluminum sulfate containing free aluminum ions, had their rheological operation windows shortened to 3.4 minutes and 2.7 minutes, respectively. The materials had lost their macroscopic fluidity and could not be formed by the 15-minute mark.

[0078] A comparison of data from the examples and comparative examples shows that the steric hindrance structure of propylene carbonate restricts its hydrolysis reaction under alkaline conditions at room temperature, and the coordination masking of metal ions by the citric acid complex shields Al. 3+ The reactivity of the reaction is enhanced by the simultaneous absence of free protons and free metal crosslinking nodes, which inhibits premature dehydration and condensation of silicates at room temperature, maintains the flow stability of the high-alkalinity water glass system and lignin molecular chains, and meets the normal operation requirements of large-scale mixing and molding equipment.

[0079] Test Example 5: The finished briquettes prepared in Examples 1 to 5 and Comparative Examples 1, 3 and 5 were randomly selected. Samples with obvious molding defects on the surface were removed. 30 complete briquettes were retained from each group as test objects and divided into two groups for drop strength and cold compressive strength determination.

[0080] When conducting the drop strength test, take one coal briquette ball each time and place it at a vertical height of 2.0 meters above a flat cast iron plate with a thickness of 20mm. Let it fall freely from a stationary state to impact the iron plate.

[0081] Inspect the condition of the briquettes after each impact. If a briquette develops a through-crack or loses more than 10% of its original mass, it is considered to have broken. Record the number of drops the briquettes could withstand before breaking. Test 15 samples in each group, and take the arithmetic mean as the drop strength test result for that group of briquettes, and record the standard deviation.

[0082] When conducting cold compressive strength tests, the remaining 15 coal briquette samples were placed one by one at the center of the upper and lower pressure plates of the microcomputer-controlled micro universal material testing machine.

[0083] The testing machine was started, and an axial compressive load was applied to the specimen at a constant rate of 10 mm / min, while simultaneously recording the load-displacement curve. Loading was stopped when the load suddenly dropped or the specimen fractured completely, and the maximum load value at that moment was recorded as the peak compressive strength. The cold compressive strength was calculated based on the peak compressive strength and the projected area of ​​the specimen under pressure, where the projected area was calculated using the average diameter of the coal briquettes. The arithmetic mean of the 15 samples in a single group was calculated as the cold compressive strength of that group of briquettes, and the standard deviation was recorded.

[0084] Table 5. Cold physical strength test data of finished coal briquettes from the examples and comparative examples (results are expressed as averages, and the standard deviations are all less than 10% of the average). According to Table 5 and Figure 5The test data show that the briquettes prepared in the example groups exhibit corresponding mechanical advantages in impact and compressive strength. The drop strength of Examples 1 to 5 ranged from 7.8 to 10.4 cycles, and the cold compressive strength ranged from 3.12 to 4.31 MPa. Comparative Example 5, which used a heat treatment temperature of 80°C, had a drop strength of only 2.8 cycles and a compressive strength of 1.15 MPa. The difference in data indicates that the system needs a higher heat treatment temperature to promote the ring-opening hydrolysis of propylene carbonate and the dehydration and condensation reaction of water glass; when the heat treatment temperature is reduced to 80°C, the curing reaction is insufficient, making it difficult to form a complete inorganic framework structure. Comparative Example 1 did not add a composite curing precursor, and Comparative Example 3 lacked the aluminum ion coordination structure in the organic crosslinking system; their drop strengths were 3.4 and 4.5 cycles, respectively, indicating that a single component or a non-crosslinked binder network cannot provide sufficient cohesive strength and toughness buffering. The in-situ reaction in the embodiment realizes the interpenetration of the inorganic silicate skeleton and the three-dimensional network structure of organic alkali lignin, which enables the rigid inorganic support and flexible organic chain segments distributed inside the coal briquette to cooperate mechanically, thereby improving the structural stability and integrity of the formed coal block when it is subjected to external loads.

[0085] Test Example 6: In the finished briquette products prepared in Examples 1 to 5 and Comparative Examples 1 and 3, 15 briquette pellets with intact appearance were randomly selected as test samples for water resistance.

[0086] The extracted coal briquette sample was completely immersed in a constant temperature water bath containing 25°C deionized water, ensuring that the water layer thickness above the sample was not less than 30 mm, and left to soak for 24 hours.

[0087] After the soaking cycle is completed, remove the briquette sample from the water bath and use absorbent filter paper to dry the surface of the sample. Observe and record the changes in the macroscopic morphology of the sample.

[0088] The dried coal briquette sample was placed in a microcomputer-controlled micro universal testing machine, and its maximum load under pressure was tested at a constant loading rate of 10 mm / min.

[0089] Record the peak load at which the specimen fails, calculate the arithmetic mean of the compressive strength of each group of 15 specimens, and record it as the cold compressive strength after immersion in water.

[0090] The water immersion strength retention rate of the briquettes is calculated by dividing the cold compressive strength obtained after water immersion by the initial cold compressive strength of the same group in the un-water immersion state (using the test data in Test Example 5).

[0091] Table 6. Water immersion compressive strength test data of finished coal briquettes from the examples and comparative examples (n=15, results are expressed as average values, and the standard deviations are all less than 10% of the average value). According to Table 6 and Figure 6 The test results showed that the structural stability of the briquettes varied in the aqueous environment. In Comparative Example 1, the uncrosslinked sample disintegrated in the water bath, and its compressive strength decreased to zero after immersion. This was because the unreacted water glass binder was easily soluble in water, and the intrusion of water severed the capillary and van der Waals forces connecting the coal particles. Comparative Example 3 showed a water strength retention rate of 40.9%, and the water turned brown after immersion, indicating that the water glass-alkali lignin curing system lacking aluminum ion coordination crosslinking possessed a certain degree of insolubility, but failed to prevent the loss of insufficiently crosslinked water-soluble alkali lignin, leading to increased internal porosity and localized stress concentration. The briquettes from Examples 1 to 5 maintained the integrity of their macroscopic morphology after 24 hours of immersion, with compressive strengths ranging from 2.51 to 3.76 MPa, and a strength retention rate exceeding 80%. The test data showed that the inorganic condensation and organic coordination reactions initiated during heat treatment jointly constructed a water-stable interpenetrating crosslinked network. The cross-linked network is distributed in the pores inside the briquettes and encapsulates solid particles, reducing the dissolution and migration of uncured water-soluble components by moisture and reducing the continuous destructive channels formed after moisture intrusion. At the same time, the aluminum-lignin related coordination structure maintains good structural stability in the aqueous medium, thereby maintaining the mechanical transfer capacity of the bonding system under wet conditions.

[0092] Test Example 7: Fifteen samples of briquettes with intact external morphology were selected from Examples 1 to 5, Comparative Examples 1 and 3, and 15 samples were retained from each group.

[0093] Each group of samples was placed inside a corundum boat and placed in the center of the isothermal zone of an atmosphere-protected tube furnace.

[0094] The closed tubular furnace chamber is purged with high-purity nitrogen to purge the air inside the furnace, and the nitrogen flow rate is stably controlled at 200 mL / min to maintain the system in a slightly positive pressure operating state.

[0095] Start the heating program, set the heating rate to 10℃ / min, heat from room temperature to 800℃, and then bake at that temperature for 30 minutes.

[0096] After the calcination stage, heating was stopped, and the sample was allowed to cool naturally to room temperature under a nitrogen atmosphere.

[0097] Remove the cooled specimen and record its macroscopic morphological characteristics. Place the specimen in a computer-controlled universal testing machine and apply uniaxial loading at a compression rate of 5 mm / min, recording the maximum load value at which structural failure occurs. Calculate the arithmetic mean of the compressive strength of the 15 specimens in a single group, and record it as the residual compressive strength after high-temperature calcination.

[0098] Table 7. Physical state and compressive strength data of coal briquettes from the examples and comparative examples after roasting at 800℃ (n=15, results are expressed as averages, and the standard deviations are all less than 10% of the average). According to Table 7 and Figure 7 The test results showed that the mechanical properties of each group of briquettes deteriorated after being treated at 800℃ in an oxygen-free environment, but the degree of degradation varied. The sample in Comparative Example 1 underwent structural collapse at high temperature, with a residual strength of only 0.21 MPa, indicating that the free bonding system lost its binding force at high temperatures. The sample in Comparative Example 3 developed multiple through-cracks and crumbled at the edges, with its strength decreasing to 0.68 MPa. This phenomenon was caused by the lack of an aluminum ion-mediated cross-linked skeleton in Comparative Example 3. Free lignin underwent pyrolysis and carbonization at high temperatures, producing a large amount of volatiles. Simultaneously, the single inorganic silicate skeleton underwent localized melting and shrinkage after exceeding its softening point, leading to stress concentration in the internal pores and a significant decrease in the skeleton's load-bearing capacity.

[0099] Examples 1 to 5 retained a relatively complete bulk structure after calcination, with residual compressive strength maintained in the range of 1.86 to 2.92 MPa. Test results showed that the interpenetrating crosslinked network constructed in the examples altered the high-temperature response mechanism of the material. During the heating process, the carbon skeleton in the organic coordination network increased the char residue rate due to crosslinking constraints during pyrolysis, preserving the porous support structure. Simultaneously, the polyvalent aluminum species in the coordination network participated in the rearrangement and reinforcement of the silicate network at high temperatures, which is beneficial to improving the stability of the high-temperature residual inorganic skeleton. The rigid inorganic skeleton and the carbonized skeleton maintained spatial synergistic support at high temperatures, resisting volumetric cracking deformation caused by thermal stress, demonstrating application potential to meet the thermal strength requirements of briquettes entering the furnace in coal gasification processes or blast furnace smelting processes.

[0100] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A coal briquette preparation process, characterized in that, Made from raw materials comprising the following parts by weight: Powdered coal: 100 parts; Powdered alkali lignin: 2-5 parts; Liquid water glass: 3-6 parts; Propylene carbonate: 0.3–0.8 parts; Citric acid chelated aluminum solution: 0.5–1.2 parts; And add water; The preparation process includes the following steps: S1. Dry mixing: The raw coal powder and powdered alkali lignin weighed according to the proportion are added to the mixer for dry mixing; S2. Wet mixing: Simultaneously spray the liquid water glass, propylene carbonate, aluminum chelate citrate solution and water into the dry mixture, and continuously wet mix at a controlled temperature to obtain a wet mixture. S3. Molding: The wet mixture is fed into a molding device and pressed under pressure to obtain wet-based coal briquettes; S4. Solidification: The wet coal briquettes are transported to a drying device and heat-treated at a set inlet air temperature. S5. Cooling: The heat-treated briquettes are cooled by forced air cooling and then screened to obtain the finished briquettes.

2. The coal briquette preparation process according to claim 1, characterized in that, The raw coal powder has a particle size ≤3.0mm, of which the mass fraction of particles with a particle size ≤1.0mm is ≥70wt%; the liquid water glass has a modulus of 2.4~3.2 and a Baume degree of 40Bé~45Bé; the powdered alkali lignin has a number average molecular weight of 3000g / mol~5000g / mol, and the pH value of a 1wt% aqueous solution of powdered alkali lignin is 9.5~11.

0.

3. The coal briquette preparation process according to claim 1, characterized in that, The citric acid chelated aluminum solution is prepared by the following steps: A1. Prepare a citric acid aqueous solution with a mass concentration of 30 wt%; A2. Under mechanical stirring at room temperature, add aluminum sulfate crystals octadechydrate until completely dissolved to form an acidic complex solution with a molar ratio of aluminum ions to citric acid molecules of 1:(1.5~2.0); A3. Under the condition of maintaining the system temperature not exceeding 30°C, slowly add a 20wt% sodium hydroxide aqueous solution to the acidic complex solution. Stop adding the solution when the pH value of the system rises to 10.5-11.0, and continue stirring at 30°C for 60 minutes to obtain a citrate chelated aluminum solution.

4. The coal briquette preparation process according to claim 1, characterized in that, Before weighing the raw coal powder, the raw coal powder is dried and homogenized in advance so that the initial moisture content of the raw coal powder when it is actually fed is controlled to be 3.0wt% to 5.0wt%.

5. The coal briquette preparation process according to claim 1, characterized in that, In step S1, the mixer is a twin-shaft paddle mixer with a rotation speed of 40 r / min to 60 r / min and a dry mixing time of 3 min to 5 min.

6. The coal briquette preparation process according to claim 1, characterized in that, In step S2, the water cooling system is turned on to control the material mixing temperature to 20℃~30℃; the amount of water to be added is calculated based on the measured initial moisture content of the raw coal powder and the moisture content of the liquid components, so that the moisture content of the wet mixture is 8.0wt%~12.0wt%, and the wet mixing time is 10 minutes~15 minutes.

7. The coal briquette preparation process according to claim 1, characterized in that, In step S3, a double-roller briquetting machine is used as the forming equipment, with the pressing linear pressure set to 20MPa~30MPa and the roller speed set to 10r / min~15r / min.

8. The coal briquette preparation process according to claim 1, characterized in that, In step S4, a mesh belt through-flow dryer is used as the drying equipment, with the inlet air temperature set at 110℃~130℃ and the heat treatment time at 25 minutes~45 minutes; at the end of the heat treatment, the center temperature of the briquettes is controlled to reach above 95℃.

9. The coal briquette preparation process according to claim 1, characterized in that, In step S5, the solidified briquettes enter the counter-current cooling section, where the center temperature of the briquettes is reduced to below 40°C under forced air cooling, and the moisture content of the finished briquettes is ≤3.0wt%.